The New OECD International Trade Model - Pain, Nigel (OECD Economics Department Working Papers, 2005)
This paper provides a detailed description of recent research to re-estimate and re-specify the international trade volume and price equations that are used in the OECD Economics Department to analyse international trade developments. New panel data estimates of the factors affecting export performance, import penetration and exchange rate pass-through into trade prices are reported for both OECD and non-OECD economies. The model set out has already been used successfully to monitor the global consistency of the international trade projections in the Economic Outlook